Al Capone Does My Shirts - Choldenko, Gennifer (New York Scholastic, 2004)
A twelve-year-old boy named Moose moves to Alcatraz Island in 1935 when guards' families were housed there, and has to contend with his extraordinary new environment in addition to life with his autistic sister.